Monitoring of Francisella noatunensis subsp. orientalis in farmed Nile tilapia (Oreochromis niloticus) in Brazil - Rodrigues, Marianna Vaz [UNESP]; Francisco, Claire Juliana [UNESP]; David, Gianmarco S.; da Silva, Reinaldo José [UNESP]; Falcone-Dias, Maria Fernanda; Júnior, João Pessoa Araújo [UNESP] (Springer Nature, 2018)
Francisella noatunensis orientalis is a bacterium that causes emerging bacteriosis in Nile tilapia (Oreochromis niloticus) in many parts of the world, including Brazil. It is a non-motile, Gram-negative, strictly aerobic, facultative intracellular coccobacillus. This species of bacteria is responsible for low to high mortality in fish farms, causing economic losses for fish farmers. This study aimed to detect the presence of F. noatunensis orientalis using qPCR (real-time polymerase chain reaction) and to describe lesions caused by the bacterium in O. niloticus in Brazilian aquaculture. For this purpose, 360 fish from six fish farms (30 per farm) were sampled at two time points (n = 180 per sampling). Necropsies and histopathology were performed for lesion observation, in addition to qPCR and sequencing for detection and identification of Francisella species. Environmental data were collected using a multiparameter sonde YSI EXO2. All measured limnological variables were within the optimum range for cultivation of Nile tilapia. The major lesions present were melanization of the skin, splenomegaly, granulomas, and inflammatory cell responses. The prevalence of francisellosis varied from 0 to 86.66% between time periods and fish farms analyzed, and an outbreak was observed during the second sampling period. This study describes the prevalence of francisellosis in O. niloticus and reports that the lesions found are not exclusively associated with this bacterial disease.
Keywords: Bacterial diseases; Francisellosis; Outbreak; qPCR